2019
DOI: 10.7717/peerj.7311
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore corridors sustain genetic footprint in plant populations: a case for Spanish drove roads

Abstract: Habitat fragmentation is one of the greatest threats to biodiversity conservation and ecosystem productivity mediated by direct human impact. Its consequences include genetic depauperation, comprising phenomena such as inbreeding depression or reduction in genetic diversity. While the capacity of wild and domestic herbivores to sustain long-distance seed dispersal has been proven, the impact of herbivore corridors in plant population genetics remains to be observed. We conducted this study in the Conquense Dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…In this sense, several studies have showed the role that herbivores plays in seed dispersal in gypsum specialists (Pueyo et al, 2008). Sheep seem to have a remarkable effect in the short and long-distance seed dispersal (Manzano & Malo, 2006;García-Fernández et al, 2019), even when seeds do not have the appropriate surface structures (e.g., seed hooks; Bakker et al, 1996;Kuiters & Huiskes, 2010). Foraging dynamics could profoundly affect the structure of the whole landscape since sheep can graze remnants in an unpredictable pattern and occurs variably as a function of the season and palatable biomass.…”
Section: Genetic Structure and Association With Environmental Variablesmentioning
confidence: 99%
“…In this sense, several studies have showed the role that herbivores plays in seed dispersal in gypsum specialists (Pueyo et al, 2008). Sheep seem to have a remarkable effect in the short and long-distance seed dispersal (Manzano & Malo, 2006;García-Fernández et al, 2019), even when seeds do not have the appropriate surface structures (e.g., seed hooks; Bakker et al, 1996;Kuiters & Huiskes, 2010). Foraging dynamics could profoundly affect the structure of the whole landscape since sheep can graze remnants in an unpredictable pattern and occurs variably as a function of the season and palatable biomass.…”
Section: Genetic Structure and Association With Environmental Variablesmentioning
confidence: 99%
“…Dispersal by large herbivores also facilitates a range of ecological processes including pollination and seed dispersal (Corlett, 2013;Dirzo et al, 2014;Rey Benayas and Bullock, 2015). Where wild large herbivores have been lost from the landscape, it is important to ensure that the use of domestic livestock reproduces the movement patterns, large and small scale in space and time, of those wild species (García-Fernández et al, 2019). This can include active herding the ensures that ecological processes are restored or maintained.…”
Section: Dispersal and Connectivitymentioning
confidence: 99%
“…In this sense, several studies have showed the role that herbivores plays in seed dispersal in gypsum specialists (Pueyo et al 2008). Sheep seem to have a remarkable effect in the short and long-distance seed dispersal (Manzano & Malo, 2006;García-Fernández et al 2019), even when seeds do not have the appropriate surface structures (e.g. seed hooks; Bakker et al 1996).…”
Section: Genetic Structure and Association With Environmental Variablesmentioning
confidence: 99%